HvAKT2 and HvHAK1 confer drought tolerance in barley through enhanced leaf mesophyll H+ homoeostasis. Issue 8 (24th January 2020) - Feng, Xue; Liu, Wenxing; Qiu, Cheng‐Wei; Zeng, Fanrong; Wang, Yizhou; Zhang, Guoping; Chen, Zhong‐Hua; Wu, Feibo
Summary: Plant K + uptake typically consists low—affinity mechanisms mediated by Shaker K + channels (AKT/KAT/KC) and high‐affinity mechanisms regulated by HAK/KUP/KT transporters, which are extensively studied. However, the evolutionary and genetic roles of both K + uptake mechanisms for drought tolerance are not fully explored in crops adapted to dryland agriculture. Here, we employed evolutionary bioinformatics, biotechnological and electrophysiological approaches to determine the role of two important K + transporters HvAKT2 and HvHAK1 in drought tolerance in barley. HvAKT2 and HvHAK1 were cloned and functionally characterized using barley stripe mosaic virus‐induced gene silencing (BSMV‐VIGS) in drought‐tolerant wild barley XZ5 and agrobacterium‐mediated gene transfer in the barley cultivar Golden Promise. The hallmarks of the K + selective filters of AKT2 and HAK1 are both found in homologues from strepotophyte algae, and they are evolutionarily conserved in strepotophyte algae and land plants. HvAKT2 and HvHAK1 are both localized to the plasma membrane and have high selectivity to K + and Rb + over other tested cations. Overexpression of HvAKT2 and HvHAK1 enhanced K + uptake and H + homoeostasis leading to drought tolerance in these transgenic lines. Moreover, HvAKT2‐ and HvHAK1‐ overexpressing lines showed distinct response of K +, H + and Ca 2+ fluxes across plasma membrane and production of nitric oxide and hydrogen peroxide in leaves as compared to the wild type and silenced lines. High‐ and low‐affinity K + uptake mechanisms and their coordination with H + homoeostasis play essential roles in drought adaptation of wild barley. These findings can potentially facilitate future breeding programs for resilient cereal crops in a changing global climate.